Microsoft SharePoint 2010 development with Visual Studio 2010 : expert cookbook : develop, debug, and deploy business solutions for SharePoint applications using Visual Studio 2010 /: expert cookbook : develop, debug, and deploy business solutions for SharePoint applications using Visual Studio 2010. (2011) - Unknown
No abstract available